Discontinuous vacuum furnace crucible support ring - CHEN WEI; CAO JINGSONG; JIAN AIHUA; CHEN HAO; ZHU KUNHONG; SU BIN; DAI WEIPING; SHAO YANBIN; SHAO DAN; HUANG DAOZE (2016)
The utility model provides a discontinuous vacuum furnace crucible support ring, includes annular crucible support ring (1), establishes in crucible support ring (1) inboard support annular boss (2) in upper end, in inside support ring cavity (3) that form of crucible support ring (1). The beneficial effects of the utility model are that: make the heating area of crucible increase, the whole board radiation range that generate heat that get into in crucible bottom have reduced the crucible because the heating area undersize causes stress inhomogeneous, have prolonged the crucible life -span. The crucible external diameter equals can be less than support ring bore diameter even approximately, can the more high -power higher board that generates heat of usable floor area under the condition of the equal size of crucible for the distillation temperature increases, thereby can distill the high boiling point alloy. 种间断式真空炉坩埚支撑环，包括环形的坩埚支撑环(1)，设在坩埚支撑环(1)上端内侧的支撑环凸台(2)，在坩埚支撑环(1)内部形成的支撑环腔体(3)。本实用新型的有益效果是：使得坩埚的受热面积增加，坩埚